2015
DOI: 10.5861/ijrsp.2015.1208
|View full text |Cite
|
Sign up to set email alerts
|

Religious song as a facilitator of prosocial behavior

Abstract: Religion plays an important role in human life. In a recent review, religiosity has been associated with prosocial behavior; although consistent, the association was weak (Saroglou, 2013). To understand religious prosociality, varying theoretical contentions were offered (Preston, Salomon, & Ritter, 2013). The present study tested Supernatural Monitoring Hypothesis and sought to identify the role of the thought of a watching God in a religious individual's prosocial behavior. With this aim, an experiment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…For example, when primed with “God”, participants provided more monetary allocations in an anonymous economic game (Shariff & Norenzayan, 2007). University students who were primed with a watching God through listening to an English song and then translating it into one’s language offered more time for volunteer work compared to those who did not listen to and did not translate a religious song (Batara, 2016). Word primes related to religion also increased intention to help (Pichon, Boccato, & Saroglou, 2007), willingness to volunteer (Sasaki et al, 2013), and honesty (Randolph-Seng & Nielsen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when primed with “God”, participants provided more monetary allocations in an anonymous economic game (Shariff & Norenzayan, 2007). University students who were primed with a watching God through listening to an English song and then translating it into one’s language offered more time for volunteer work compared to those who did not listen to and did not translate a religious song (Batara, 2016). Word primes related to religion also increased intention to help (Pichon, Boccato, & Saroglou, 2007), willingness to volunteer (Sasaki et al, 2013), and honesty (Randolph-Seng & Nielsen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These experiments used the music priming paradigm of Batara (2016). The Christian music condition had participants listen to the Christian hymn “Rock of Ages.” The neutral song in the control condition was “Twinkle Twinkle Little Star.”…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the music primes (3a and 3b), one major limiting factor is that unlike Batara (2016), the experiments were conducted in an online setting. Due to this, there was no way to ensure participants would adequately listen to the songs.…”
Section: H4 Religiosity Does Not Decrease Analytic Thinkingmentioning
confidence: 99%
“…The results of her research revealed that the folk song entitled Manuk Dadali can foster the spirit of nationalism. Batara (2016) argues that religious songs can be a medium for shaping prosocial behavior. Regarding song as a learning medium, Supartini et al (2020) study shows that the song-based learning method has a level of validity, practicality, and effica-cy above the benchmark for developing children's cognitive and psychomotor elements.…”
Section: Introductionmentioning
confidence: 99%